2012
DOI: 10.1002/ejoc.201200202
|View full text |Cite
|
Sign up to set email alerts
|

Selective N‐Alkylation of Arylamines with Alkyl Chloride in Ionic Liquids: Scope and Applications

Abstract: An efficient N-selective alkylation of primary aromatic\ud amines in molten quaternary ammonium salts, as the solvent,\ud under relatively mild and base-free conditions is presented.\ud On the basis of the Kamlet–Taft parameters and the nucleophilicity\ud of the IL (ionic liquid) anions, the influence of the ionic liquid was evaluated. This protocol was validated on a\ud larger multigram scale and with the syntheses of bioactive\ud heterocycles (e.g., 1,4-benzothiazine and quinoxalines) and\ud new efficient MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 85 publications
0
12
0
1
Order By: Relevance
“…However, despite the number of protocols devoted to the oxidative homocondensation of amines, carrying out these reactions in environmentally friendly solvents remains unexplored, and, to the best of our knowledge, no examples of successful methods performed in ionic liquids (ILs)14 have been reported until now. Continuing our interest in the use of ILs in organic synthesis,15 we recently found that the N ‐alkylation of arylamines with alkyl chlorides can be performed in high yields and with high selectivities in molten tetraalkylammonium salts at 100 °C 15d. However, this reaction is not applicable to benzylamines, since appreciable amounts of the corresponding homocondensed imines were detected in addition to the alkylation product.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the number of protocols devoted to the oxidative homocondensation of amines, carrying out these reactions in environmentally friendly solvents remains unexplored, and, to the best of our knowledge, no examples of successful methods performed in ionic liquids (ILs)14 have been reported until now. Continuing our interest in the use of ILs in organic synthesis,15 we recently found that the N ‐alkylation of arylamines with alkyl chlorides can be performed in high yields and with high selectivities in molten tetraalkylammonium salts at 100 °C 15d. However, this reaction is not applicable to benzylamines, since appreciable amounts of the corresponding homocondensed imines were detected in addition to the alkylation product.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, MALDI MS has become a technique of considerable impact on many fi elds, from proteomics [ 11 , 12 ] to lipidomics [ 13 , 14 ] and, more recently, even metabolomics due to the introduction of new matrices such as ionic liquids [ 15 , 16 ], proton sponges [ 17 ] or aromatic amines [ 18 ], and metal nanoparticles [ 19 , 20 ].…”
Section: Food Analysis By Mass Spectrometrymentioning
confidence: 99%
“…[4,5] In the past decades, many methods have been developed for the synthesis of N-alkylated amines, including the employments of alcohols, alkylbromide, [31,32] nitriles, [33,34] aldehydes, [1] alkyl halides, [35][36][37][38][39] allyl and benzyl halides, [36,39] R-NH 2 ·HBr and alkyl bromides, [40] carboxylic acids [41] and dialkylboron triflates. [42] In recent years, organic azides have been considered to be valuable intermediates in the synthesis of N-alkylated anilines in spite of their explosive features.…”
Section: Introductionmentioning
confidence: 99%